Implementing Energy-as a Common approach in the revitalization of shrinking cities - Simone Di Pietro (Belgeo)
The new attempts to implement green transformations of the economy aimed at sustainability coexist with the passage from the Fordist to the post-Fordist era, contributing to create profound territorial transformations throughout the world. Although the current economic crisis is slowing the process of energy transition at the global level, the definition of the future economic structure of territories will be strictly connected to the spatial effects of energy transitions and their intensive land use processes, given the low-power nature of renewable energy sources. Urban centres are the places where these changes are reflected most quickly and clearly, being the centres of major economic activities. In this regard, urban areas experiencing progressive economic marginalisation with consequent depopulation, face sustainability issues regarding energy use and maintenance of the existing infrastructure. With the aim of clarifying the role of shrinking cities within these transformations, a theoretical contribution is presented considering different approaches to co-production of energy transition processes in them.